2010
DOI: 10.5194/acp-10-10187-2010
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of HO<sub>x</sub>, NO<sub>x</sub> and halogen chemistry in the antarctic boundary layer

Abstract: A modelling study of radical chemistry in the coastal Antarctic boundary layer, based upon observations performed in the course of the CHABLIS (Chemistry of the Antarctic Boundary Layer and the Interface with Snow) campaign at Halley Research Station in coastal Antarctica during the austral summer 2004/2005, is described: a detailed zero-dimensional photochemical box model was used, employing inorganic and organic reaction schemes drawn from the Master Chemical Mechanism, with additional halogen (iodine and br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 94 publications
3
63
0
Order By: Relevance
“…Many questions remain on the mechanism of release of chlorine/bromine species from the snowpack (see Abbatt et al, 2012, for a detailed review). An important issue is whether it can explain observed HO x and NO x levels (SaizLopez et al, 2008;Bloss et al, 2010), as well as observed halogens levels. A modelling study by Thomas et al (2011Thomas et al ( , 2012 indicated that up to 10 ppt of tropospheric BrO can be explained by a mechanism involving nitrate formation in the interstitial snow; if this is the case, the resulting formation of NO x may compensate for the depletion of O 3 due to reactive Br, possibly leading to net ozone formation.…”
Section: P S Monks Et Al: Tropospheric Ozone and Its Precursorsmentioning
confidence: 99%
“…Many questions remain on the mechanism of release of chlorine/bromine species from the snowpack (see Abbatt et al, 2012, for a detailed review). An important issue is whether it can explain observed HO x and NO x levels (SaizLopez et al, 2008;Bloss et al, 2010), as well as observed halogens levels. A modelling study by Thomas et al (2011Thomas et al ( , 2012 indicated that up to 10 ppt of tropospheric BrO can be explained by a mechanism involving nitrate formation in the interstitial snow; if this is the case, the resulting formation of NO x may compensate for the depletion of O 3 due to reactive Br, possibly leading to net ozone formation.…”
Section: P S Monks Et Al: Tropospheric Ozone and Its Precursorsmentioning
confidence: 99%
“…In this work we use a chemistry scheme based on a subsection of the hydrocarbons (ethane, propane, iso-butane, n-butane, iso-pentane, n-pentane, hexane, ethene, propene, 1-butene, acetylene, isoprene, toluene, benzene, methanol, acetone, acetaldehyde and DMS) available from the Master Chemical Mechanism version 3.2 (MCM v3.2 http://mcm.leeds.ac.uk/MCM/home.htt) Saunders et al, 2003), with a halogen chemistry scheme described by Saiz-Lopez et al (2006), Whalley et al (2010) and Edwards et al (2011). We also include the reaction between OH and CH 3 O 2 (Bossolasco et al, 2014;Fittschen et al, 2014;Assaf et al, 2016;Yan et al, 2016), with a rate coefficient of 1.6 × 10 −10 cm 3 s −1 (Assaf et al, 2016) and products HO 2 + CH 3 O (Assaf et al, 2017), the impact of which on the HO 2 : OH ratio and CH 3 O 2 budget is described in the Supplement. The total number of species in the model is ∼ 1200, with ∼ 5000 reactions.…”
Section: Constrained Box Modelmentioning
confidence: 99%
“…Emissions for CH 3 I follow Bell et al (2002), while those of other organic iodine species use parameterisations based on chlorophyll a in the tropics and constant oceanic and coastal fluxes in extratropical regions (Ordonez et al, 2012). Emissions of inorganic iodine species (HOI and I 2 ) use the results of Carpenter et al (2013), with oceanic iodide concentrations parameterised by MacDonald et al (2014). The iodine chemistry scheme includes 26 unimolecular and bimolecular reactions, 3 three-body reactions, 21 photolysis reactions and 7 heterogeneous reactions, using recommendations by Atkinson et al (2007) and Sander et al (2011) where available.…”
Section: Global Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…suggested that halogen may be present at Summit, perturbing the HO x cycling and enhancing OH levels. In contrast, a later study at Halley Bay, Antarctica (75 • 35 S, 26 • 19 W) found average OH levels of 3.9 × 10 5 molec cm −3 in February with typical maximum (local noontime) levels of 7.9 × 10 5 molec cm −3 (Bloss et al, 2007(Bloss et al, , 2010. The OH levels at Halley Bay were slightly higher than measured at Palmer station in the same season of the year but significantly lower than observed at South Pole.…”
Section: Introductionmentioning
confidence: 81%